2021
DOI: 10.1016/j.isci.2021.103440
|View full text |Cite
|
Sign up to set email alerts
|

A new murine esophageal organoid culture method and organoid-based model of esophageal squamous cell neoplasia

Abstract: Summary Organoids mimic the physiologic and pathologic events of organs. However, no consensus on esophageal organoid (EO) culture methods has been reached. Moreover, organoid models reproducing esophageal squamous cell carcinoma (ESCC) initiation have been unavailable. Herein, we sought to develop an esophageal minimum essential organoid culture medium (E-MEOM) for culturing murine EOs and establishing an early ESCC model. We formulated E-MEOM to grow EOs from a single cell with clonal expansion, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…Similar to our study ( Zheng et al., 2021 ), adenoviral vector transduction into mouse intestinal organoids is feasible ( Wang et al., 2014 ), and this method was successful in our previous study ( Zheng et al., 2021 ). According to our previous report, the viral infection efficiency was more than 80% when we measured the GFP-positive cells in the microscope.…”
Section: Expected Outcomessupporting
confidence: 75%
See 4 more Smart Citations
“…Similar to our study ( Zheng et al., 2021 ), adenoviral vector transduction into mouse intestinal organoids is feasible ( Wang et al., 2014 ), and this method was successful in our previous study ( Zheng et al., 2021 ). According to our previous report, the viral infection efficiency was more than 80% when we measured the GFP-positive cells in the microscope.…”
Section: Expected Outcomessupporting
confidence: 75%
“…We usually perform the passaging 8–10 days after seeding 1,000 cells on the 48-well plate. We have reported that the average size of the EOs is around 25,000 μm 2 at Day 10 in the microscopic images ( Zheng et al., 2021 ). If different scales of culture are used, the morphology of EOs and the culture medium should be carefully monitored.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 3 more Smart Citations